2008
DOI: 10.1007/s10616-008-9131-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of inhibitory effect and apoptosis induction of Zyzyphus Jujube on tumor cell lines, an in vitro preliminary study

Abstract: In the present study, water extract of dried fruit of Zyzyphus Jujube was tested for its possible anticancer effect and induction of apoptosis on human tumor cell lines, HEp-2, HeLa and Jurkat cell lines. The inhibitory effect of water extract of this fruit on cell proliferation was assessed by MTT colorimetric assay. The induction of apoptosis of this extract was analyzed by DNA fragmentation analysis. Zyzyphus Jujube extract showed inhibitory effects on mentioned cell lines. Jurkat leukemic line was found th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
48
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 19 publications
3
48
1
Order By: Relevance
“…In addition, the authors claimed that apoptosis induction is one of the mechanisms of action associated with increased caspase-3 and caspase-9 activities (12). Apoptosis induction was also observed in the present study, which is in congruence with the previous findings in this regard (7,10,11). Apoptosis is a vital component of normal cell turnover in body tissues, which normally occurs during development and aging, and its inhibition is considered to be an important factor in many cancers (32-34, 41, 42).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In addition, the authors claimed that apoptosis induction is one of the mechanisms of action associated with increased caspase-3 and caspase-9 activities (12). Apoptosis induction was also observed in the present study, which is in congruence with the previous findings in this regard (7,10,11). Apoptosis is a vital component of normal cell turnover in body tissues, which normally occurs during development and aging, and its inhibition is considered to be an important factor in many cancers (32-34, 41, 42).…”
Section: Discussionsupporting
confidence: 92%
“…For instance, Huang et al reported the anticancer activities and apoptosis induction of the Z. jujuba fruit in human hepatoma cells (10). Findings of a study investigating the effects of Z. jujuba on HeLa, Hep-2, and leukemia cells showed similar results (11). In addition, previous studies have confirmed the anti-proliferative and apoptotic effects of bioactive constituents of the Z. jujuba fruit extract (especially triterpenes) on breast cancer cell lines (MCF-7 and SKBr3) (7).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Jujube has also recently come into prominent use as an ingredient in processed foods such as drinks and tea granules in Korea (2,3). Furthermore, jujube is also used as traditional medicine in Korea (4), where it is reported to possess numerous health-promoting benefits such as antioxidant activity (5), anticancer effects (6), and hepatoprotective effects (7).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have reported the antioxidant capacity and beneficial health effects of Z. jujuba, including towards AD (1,(5)(6)(7)15). It was previously reported that Z. jujuba fruits had procyanidin B2, epicatechin, quercetin 3-O-rutinoside, quercetin 3-O-galactoside, kaempferolglucosyl-rhamnoside, whereas Z. jujuba seeds contained saponarin, spinosin, vitexin, swertish, 6'''-hydroxybenzoylspinosin, and 6'''-feruloylspinosin (16).…”
Section: Introductionmentioning
confidence: 99%